UPAYA MENINGKATKAN KETERAMPILAN SOSIAL ANAK USIA 4-5 TAHUN MELALUI PERMAINAN PETAK UMPET (PENELITIAN TINDAKAN KELAS DI PAUD AISYAH JONGGOL, KABUPATEN BOGOR) - Meli, Meli; Nur Masturah, Sabila; Pujianti, Yuli (LPPM Sekolah Tinggi Ilmu Tarbiyah Al Marhalah Al Ulya Bekasi, Indonesia, 2022)
This study aims for improve the social skills of children aged 4-5 years through a game of hide and seek in Aisyah Early Childhood Education, Bogor, which will be held in October 2021. The method used in this research is action research which is carried out through two cycles. The cycle consists of planning, action, observation, reflection. The research subjects were seven children of group A in Aisyah Early Childhood Education aged 4-5 years who had problems in social skills. Research data were collected using observations in the form of observation guidelines and field notes, documentation, photos of activities, and interviews. Data were analyzed using a minimum percentage of 71% cycle. The results of data analysis showed that the score of social skills in cycle 2 was declared successful. Based on these results it was determined that the game of hide and seek can improve the social skills between 4-5 years old. The implication of this research is that playing the game of hide and seek can be used as an alternative learning method to improve the social skills of children aged 4-5 years. Thus, it is hoped that early childhood researchers can use the hide-and-seek method in improving children's social skills optimally.